2021
DOI: 10.3389/fcvm.2021.752769
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Cerebral Ischemia After Subarachnoid Hemorrhage: Is There a Relevant Experimental Model? A Systematic Review of Preclinical Literature

Abstract: Delayed cerebral ischemia (DCI) is one of the main prognosis factors for disability after aneurysmal subarachnoid hemorrhage (SAH). The lack of a consensual definition for DCI had limited investigation and care in human until 2010, when a multidisciplinary research expert group proposed to define DCI as the occurrence of cerebral infarction (identified on imaging or histology) associated with clinical deterioration. We performed a systematic review to assess whether preclinical models of SAH meet this definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 119 publications
1
14
0
Order By: Relevance
“…36,37 Whatever the immediate trigger of the inflammatory response to aSAH may be, the concept of NET-induced thrombus formation as a result of it is intriguing, as it provides a framework that links inflammation, thrombus formation, and DCI. 5,38 We found high levels of MPO-DNA complexes in all patients with aSAH, not only in those with DCI. While lower levels of MPO-DNA complexes have been measured in the general population 39 , the high levels in our study may reflect an overall inflammatory environment after aSAH, in line with high levels of C-reactive protein in all our patients.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…36,37 Whatever the immediate trigger of the inflammatory response to aSAH may be, the concept of NET-induced thrombus formation as a result of it is intriguing, as it provides a framework that links inflammation, thrombus formation, and DCI. 5,38 We found high levels of MPO-DNA complexes in all patients with aSAH, not only in those with DCI. While lower levels of MPO-DNA complexes have been measured in the general population 39 , the high levels in our study may reflect an overall inflammatory environment after aSAH, in line with high levels of C-reactive protein in all our patients.…”
Section: Discussionmentioning
confidence: 67%
“…36,37 Whatever the immediate trigger of the inflammatory response to aSAH may be, the concept of NET-induced thrombus formation as a result of it is intriguing, as it provides a framework that links inflammation, thrombus formation, and DCI. 5,38…”
Section: Discussionmentioning
confidence: 99%
“…There is also data to suggest that free heme itself may lead to endothelial injury, which in turn may promote recruitment of macrophages and neutrophils (41). As a downstream mechanism, the concept of NET-induced thrombus formation is intriguing, as it provides a framework that links inflammation, thrombus formation, and DCI (6,40). NETs have been therapeutically targeted in animal models and human pulmonary disease such as COVID-19, which might inform future studies assessing new treatments in patients with aSAH (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the blood-brain barrier with influx of cell-free heme into the subarachnoid space may stimulate local macrophages and the heme scavenger system, leading to further recruitment of other immune cells and excessive inflammation ( 6 , 38 ). Direct activation of neutrophils through free heme is conceivable as well, with free heme being a driving factor for NET release in sickle cell disease ( 39 , 40 ). There is also data to suggest that free heme itself may lead to endothelial injury, which in turn may promote recruitment of macrophages and neutrophils ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another complication of aSAH with limited investigation via preclinical models is delayed cerebral ischemia (DCI). A systematic review of 78 preclinical studies showed that only 38% of models (with the most prevalent method being cisterna magna injection) reproduced DCI, but these instances were never investigated with imaging [ 124 ]. Given that DCI is a major prognostic factor of poor outcomes or disability after aSAH, it is imperative to find a preclinical model that reproduces DCI well [ 124 , 125 ].…”
Section: Pre-clinical Findingsmentioning
confidence: 99%